Assessing General Dentists' Involvement in the Dental Treatment and Management of Diabetic Patients in the State of Kuwait - Kayed, Dena A. (جامعة الكويت - مجلس النشر العلمي, 2015)
Diabetes Mellitus (DM) currently affects more than 285 million people worldwide and is expected to affect 438 million by 2030. The dental practice setting offers an important but largely overlooked opportunity to manage diabetic patients. This study focuses on issues related to managing diabetic patients in the primary health care centers dental clinics in the State of Kuwait. We hypothesize that there is a need to increase general dental practitioners’ involvement in managing diabetic patients and that such actions can be expected to improve oral and general health outcomes. Methods: At the time where the data was collected (2010), a total of 331 general dentists were practicing in 75 primary health care centers. A cluster sampling strategy was used to draw a random sample of general dental practitioners in all five governorates. A random sample of primary health care centers in each governorate was chosen. A power analysis test concluded that the target sample size for this study was 150 subjects. Measures: Scales used in measuring general dentists’ management of diabetic patients in the primary health care centers were evaluation of the patient’s health, communication skills, and active management scales. Create three different domains: attitude perception, socio-demographics, and working environment and assess how they affect the performance of managing diabetic patients. Results: Almost all the participants agreed that it is applicable to change/ adjust the treatment plan if a patient is diabetic, and the majority agreed to screen patients for diabetes by using finger-stick tests. Socio-demographic, these outcomes clarified that many participants do not update their academic skills and knowledge through attending continuing education courses or participate in study clubs. Conclusion: The study suggests that in order to improve the management/treatment levels of diabetic patients, multiple disciplinary areas must collaborate.
Keywords: أطباء الأسنان -- مرضى السكري -- الكويت